Exploring Key External and Internal Factors Affecting State Performance in Southeast Asia - Michael Jakobsen (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2015)
The main aim of this article is to identify key external and internal factors that are capable of impacting and thus influencing directly or indirectly state performance in Southeast Asia with special emphasis on Myanmar, Vietnam and Singapore. The theoretical aim is to develop a framework for partly being able to delineate some external boundaries for state manoeuvring and partly delineate the internal size of the space or 'room' that conditions state performance in an international cum national context respectively. On the basis of the above this article thus argues that the state is sandwiched between external and internal factors as the two respectively define the outer boundaries and internal size of the room in which the state has to perform.
hdl:10398/9142
Keywords: 330; Glocalisation; State Performance; Civil Society; Southeast Asia; Myanmar; Vietnam; Singapore; Globalisierung; Regionalentwicklung; Gesellschaft; Myanmar; Singapur; Vietnam; Südostasien